Clinical Severity Classification using Automated Conjunctival Hyperemia Analysis Software in Patients with Superior Limbic Keratoconjunctivitis. (3rd June 2018) - Kurita, Junki; Shoji, Jun; Inada, Noriko; Yoneda, Tsuyoshi; Sumi, Tamaki; Kobayashi, Masahiko; Hoshikawa, Yasuhiro; Fukushima, Atsuki; Yamagami, Satoru
ABSTRACT: Purpose : Digitization of clinical observation is necessary for assessing the severity of superior limbic keratoconjunctivitis (SLK). This study aimed to use a novel quantitative marker to examine hyperemia in patients with SLK. Materials and Methods : We included six eyes of six patients with both dry eye disease and SLK (SLK group) and eight eyes of eight patients with Sjögren syndrome (SS group). We simultaneously obtained the objective finding scores by using slit-lamp examination and calculated the superior hyperemia index (SHI) with an automated conjunctival hyperemia analysis software by using photographs of the anterior segment. Three objective finding scores, including papillary formation of the superior palpebral conjunctiva, superior limbal hyperemia and swelling, and superior corneal epitheliopathy, were determined. The SHI was calculated as the superior/temporal ratio of bulbar conjunctival hyperemia by using the software. Fisher's exact test was used to compare a high SHI (≥1.07) ratio between the SLK and SS groups. P -Values < 0.05 were considered statistically significant. Results : The SHI (mean ± standard deviation) in the SLK and SS groups was 1.19 ± 0.50 and 0.69 ± 0.24, respectively. The number of patients with a high SHI (≥1.07) was significantly higher in the SLK group than in the SS group ( p < 0.05). The sensitivity and specificity of the SHI in the differential diagnosis between SS and SLK were 66.7% and 87.5%, respectively. An analysis of the association between the objective finding scores and SHI showed that the SHI had a tendency to indicate the severity of superior limbal hyperemia and swelling score in the SLK group. Conclusion : The SHI calculated using the automated conjunctival hyperemia analysis software could successfully quantify superior bulbar conjunctival hyperemia and may be a useful tool for the differential diagnosis between SS and SLK and for the quantitative follow-up of patients with SLK.